Cardiac rehabilitation and symptoms of anxiety and depression after percutaneous coronary intervention. (July 2018) - Olsen, Siv JS; Schirmer, Henrik; Wilsgaard, Tom; Bønaa, Kaare H; Hanssen, Tove A
Background: Anxiety and depression are related to coronary heart disease, and psychological support is recommended in cardiac rehabilitation. Purpose: The aims of this study were: to compare the prevalence of anxiety and depression with respect to cardiac rehabilitation participation among patients who have been treated with percutaneous coronary intervention; to examine prevalence of anxiety and depression among percutaneous coronary intervention patients compared to the general population; and to identify predictors of symptomatic anxiety and depression among percutaneous coronary intervention patients. Methods: We included 9013 patients undergoing first-time percutaneous coronary intervention. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale in a representative sample of 775 patients at baseline and after three years of follow-up, and in the entire cohort at three-year follow-up. Results: Cardiac rehabilitation participants had more anxiety and depression than cardiac rehabilitation non-participants at baseline, and both groups had a more anxiety than the general population. The levels of anxiety and depression fell significantly during three years of follow-up, but the changes did not differ between cardiac rehabilitation participants and cardiac rehabilitation non-participants. Three years after percutaneous coronary intervention the prevalence of anxiety was 32% ( p < 0.001), higher among cardiac rehabilitation participants compared to cardiac rehabilitation non-participants. Female gender and younger age were associated with anxiety, whereas older age, lower levels of education and cardiovascular morbidity were associated with depression. Conclusion: The levels of anxiety and depression were prevalent among percutaneous coronary intervention patients and the levels were not affected by cardiac rehabilitation participation. Anxiety is prevalent among female and younger patients, whereas depression is related to older age and cardiovascular co-morbidity.